2021
DOI: 10.2217/rme-2021-0032
|View full text |Cite
|
Sign up to set email alerts
|

Novel Assessment of Leukocyte-Rich Platelet-Rich Plasma on Functional and Patient-Reported Outcomes in Knee Osteoarthritis: A Pilot Study

Abstract: Background: Leukocyte-rich platelet-rich plasma (LR-PRP) has demonstrated to be beneficial for patient with knee osteoarthritis (KOA); however, reliable objective end points to accurately assess its therapeutic effects is lacking. Aim: To investigate the efficacy of LR-PRP as assessed by functional and patient-reported outcomes at early time-points (6 weeks). Materials & methods: We conducted a prospective cohort study in 12 patients with diagnosed KOA (Kellgren Lawrence score of II–III), who underwent a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…In addition to this randomized controlled trial, more recent prospective cohort studies have demonstrated that LR-PRP does indeed provide beneficial results for patients with knee osteoarthritis. 9,13,15…”
Section: Discussionmentioning
confidence: 99%
“…In addition to this randomized controlled trial, more recent prospective cohort studies have demonstrated that LR-PRP does indeed provide beneficial results for patients with knee osteoarthritis. 9,13,15…”
Section: Discussionmentioning
confidence: 99%
“…IMUs provide more detailed and necessary information about a person’s functional status comparable to a stopwatch, and are more portable and translational, compared to three-dimensional, optoelectronic-motion-capture technology. In fact, the importance of implementation has been discussed previously [ 27 , 61 ], and implementation has been attempted in another population [ 62 ]. We believe appropriate strategies, such as IMU-based, perioperative-gait assessment will significantly advance the management of diabetic foot.…”
Section: Discussionmentioning
confidence: 99%
“…IMUs provide more detailed and necessary information about a person's functional status compared to a stopwatch and are more portable and translational compared to three-dimensional optoelectronic motion capture technology. In fact, the importance of implementation has been discussed previously [23,55], and implementation has been attempted in another population [56]. We believe appropriate strategies such as IMU-based perioperative gait assessment will significantly advance the management of diabetic foot.…”
Section: Discussionmentioning
confidence: 99%